Behavioural sleep problems in previously untreated children with attention deficit hyperactivity disorder. Issue 1 (2nd January 2018) - Eyuboglu, Murat; Eyuboglu, Damla
ABSTRACT: OBJECTIVE: Although sleep symptoms are not included in the diagnostic criteria of attention deficit hyperactivity disorder (ADHD), these problems are common in children with ADHD. The presence of sleep problems was associated with impairment in functionality and increase in ADHD intensity. The aims of the study were to evaluate sleep problems of children with ADHD who had never received any psychiatric treatment and investigate the effects of these problems in functionality. METHODS: The present study included 83 children who were diagnosed as having ADHD and had never received any psychiatric treatment. The control group consisted of 106 healthy children. Psychiatric diagnostic interview was applied to all children. The parents completed the Conner's Parent Questionnaire to evaluate the intensity of ADHD in the children, the Children's Sleep Habits Questionnaire (CSHQ) to evaluate sleep problems, and the Weiss Functional Impairment Rating Scale to evaluate the functionality of the children. RESULTS: The total scores of subscale and scales of CSHQ were significantly higher in the study group. ADHD children slept 1 hour later and sleep quantity was 1.5 hours less than the control group. There was a significant correlation between sleep problems, ADHD severity, and functionality of these children. CONCLUSIONS: The results demonstrated that children with ADHD experienced more sleep problems and slept less than the children in the healthy control group, and functional impairments increased due to these problems. Another important finding is that sleep problems are not related to drug use. Maintaining sleep hygiene or interventions against sleep problems may increase sleep quality and may improve self and family functionality. Therefore, the standardized sleep evaluation must be performed in cooperation with parents in all children with ADHD.